Quantitative analysis of New Zealand-Antarctica plate motions during the Paleogene and Late Cretaceous - Chambord, Amandine (11738216) (2017)
Quantifying past motions of tectonic plates in the southwest Pacific is important because the Pacific-Antarctic ridge is the only non-destructive boundary between the Pacific plate and other major plates. However, formation of sea-ice near Antarctica impairs the collection of magnetic anomaly data that are necessary to calculate plate rotations. A detailed analysis of all ship-track magnetic data available in the southwest Pacific (61 cruises, 153 profiles, including several cruises collected after 1995) is presented here. Four different sources of uncertainty are quantified: (1) confidence of magnetic anomaly identification, (2) magnetic reversal location picking precision, (3) ship navigation precision, and (4) magnetic data quality. Finite plate rotations are calculated for the southwest Pacific (42.5 to 79 Ma) using the resulting magnetic anomaly database (1528 magnetic reversal data). Finite rotations were calculated using the Hellinger criterion, or by a new method presented here that assumes orthogonality between fracture zones and ridge segments. The new method requires less parameters and is hence able better estimate rotations in cases with an uneven distribution of sparse magnetic data. Rotations and formal uncertainties are calculated for thirty-one chrons (c20y to c33o). They confirm the existence of a three plate system (Pacific, Marie Byrd Land, Bellingshausen) in the southwest Pacific from before c31o (68.7 Ma) until c28y (62.5 Ma). After c28y, the Bellingshausen and Marie Byrd Land plates moved as a single plate.